1961
DOI: 10.1002/zaac.19613090102
|View full text |Cite
|
Sign up to set email alerts
|

Über Manganoxyde. VII. Darstellung und Eigenschaften von Braunsteinen. I (Die δ‐Gruppe der Braunsteine)

Abstract: Es wird ein kurzer Überblick über den derzeitigen Stand der Braunsteinforschung gegeben. Die Untersuchungsmethoden werden mitgeteilt.δ‐Braunsteine werden nach mehreren Verfahren hergestellt und charakterisiert. Beim Erhitzen an der Luft wandeln sich die δ‐Braunsteine bei etwa 100 °C in γ″‐MnO2 um. Bei weiterer Temperaturerhöhung entsteht β′‐MnO2, das dann in β‐MnO2 übergeht; anschließend tritt unter Sauerstoffabgabe Bildung von α‐Mn2O3 ein.Bei den „fremdionenhaltigen”︁ δ‐Braunsteinen findet beim Tempern Umwand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

1961
1961
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(25 citation statements)
references
References 53 publications
1
23
0
1
Order By: Relevance
“…(Glemser et al 1961, Regner et al 1963, Sterr et al 1969, Giovanoli et al 1970, and Yamamoto et al 1980. The chemical composition of this practically amorphous product varies between (I) -NqMn,,On.9H,O and (11) -Mn,0,33H,0 (Gmelin 1973a andGiovanoli et al 1973).…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Glemser et al 1961, Regner et al 1963, Sterr et al 1969, Giovanoli et al 1970, and Yamamoto et al 1980. The chemical composition of this practically amorphous product varies between (I) -NqMn,,On.9H,O and (11) -Mn,0,33H,0 (Gmelin 1973a andGiovanoli et al 1973).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The transformation of MnOi to MnO, can be carried out using different reductants (Gmelin 1973a, Glemser et al 1961, Regner et al 1963, Sterr et al 1969, and Giovanoli et al 1970. In most cases, hydrogen peroxide (H202) is used for this process.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Within the category of metal oxides, systems based on manganese dioxide are presently receiving considerable attention from the scientific community [6]. With a myriad of available synthesis methods [7][8][9][10][11][12][13][14], and as a result wide ranging morphologies, coupled with good faradaic electrochemical performance, low cost and environmental friendliness, this class of materials represents an interesting and promising area of research.…”
Section: Supercapacitorsmentioning
confidence: 99%
“…In the experiments of Brown et al (1971), natural birnessite changed to cryptomelane and then crystallized as hausmannite at 600°C after passing through an amorphous state. Glemser et al (1961) observed that birnessite containing foreign cations lost water at 110-125°C and converted to cryptomelane at 370-500°C and to bixbyite upon further heating. McMurdie and Golovato (1948) report that cryptomelane may convert directly to hausmannite or go through an intermediate stage of bixbyite because of impurities.…”
Section: Rooksbymentioning
confidence: 99%